2016
DOI: 10.1532/hsf.1400
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Metabolic Syndrome on Acute Kidney Injury Occurrence after Coronary Artery Bypass Grafting

Abstract: The presence of MetS seems to be associated with increased incidence of AKI after cardiac surgery. MetS is a modifiable issue; if its components are well controlled its dreadful effects after cardiac surgery might be controlled as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…The same result was obtained by Hertzberg D et al, they reported both type 1 and 2 DM were associated with an increased risk of AKI after CABG [21]. A Tekeli Kunt et al reported the presence of metabolic syndrome (hyperglycemia, dyslipidemia, abdominal obesity, and hypertension) seemed to be associated with increased incidence of AKI after CABG [22]. Oezkur et al concluded that chronic hyperglycemia defined on a single measurement of hemoglobin A1c ≥ 6.0% was also associated with the incidence of AKI after CABG.…”
Section: Discussionsupporting
confidence: 68%
“…The same result was obtained by Hertzberg D et al, they reported both type 1 and 2 DM were associated with an increased risk of AKI after CABG [21]. A Tekeli Kunt et al reported the presence of metabolic syndrome (hyperglycemia, dyslipidemia, abdominal obesity, and hypertension) seemed to be associated with increased incidence of AKI after CABG [22]. Oezkur et al concluded that chronic hyperglycemia defined on a single measurement of hemoglobin A1c ≥ 6.0% was also associated with the incidence of AKI after CABG.…”
Section: Discussionsupporting
confidence: 68%
“…The same result was obtained by Hertzberg D et al, they reported both type 1 and 2 DM were associated with an increased risk of AKI after CABG [21] . A Tekeli Kunt et al reported the presence of metabolic syndrome (hyperglycemia, dyslipidemia, abdominal obesity, and hypertension) seemed to be associated with increased incidence of AKI after CABG [22] . Oezkur et al concluded that chronic hyperglycemia de ned on a single measurement of hemoglobin A1c ≥ 6.0% was also associated with the incidence of AKI after CABG.…”
Section: Discussionmentioning
confidence: 99%
“…Included Studies). Most studies reported North America data ( n =40) 4 6 , 15 , 23 , 27 , 30 35 , 38 40 , 43 , 46 49 , 52 , 53 , 55 62 , 65 67 , 70 , 73 , 75 78 , 80 , with the remaining spanning Europe 19 , 21 , 22 , 24 , 28 , 42 , 44 , 50 , 51 , 64 , 68 , 81 , the Middle East 20 , Asia 37 , 41 , 45 , 71 , 72 , 74 , 82 , 83 , Africa 63 , and South America 54 . The assessed risk of bias of the included studies ranged from 5 to 8 (fair to good) out of a possible 9 stars when assessed using the NOS.…”
Section: Resultsmentioning
confidence: 99%
“…Across these studies, a total of 333 488 patients with MetS underwent surgery versus 1 449 817 surgical patients without MetS. We found fifteen of 44 studies reported an increased risk of mortality across a range of surgical types including bariatric 39 , 43 , 57 , cardiac 19 , 42 , ear, nose, and throat (ENT) 35 , emergency 31 , endocrine 59 , 84 , gastrointestinal 40 , hepatobiliary 23 , 33 , 34 , neurosurgery 49 , and orthopaedic 47 . Twenty-five studies considered for meta-analysis found no association with 30-day mortality between MetS and non-MetS patients across a wide range of surgical types.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation